Semi-global Simulations of Star Formation in Nuclear Rings of Barred Galaxies - Kim, Woong-Tae; Moon, Sanghyuk (Journal of physics. Conference series, 2024)
Nuclear rings at the centers of barred galaxies are active in star formation. To understand what determines the star formation rate (SFR) and structure of nuclear rings, we conduct semi-global, magnetohydrodynamic simulations of nuclear rings subject to various mass inflow rates with and without magnetic fields. We adopt the TIGRESS framework of Kim & Ostriker to handle radiative heating and cooling, star formation, and related supernova feedback. Our findings suggest that supernova feedback cannot destroy the nuclear ring completely or halt star formation within it, while both the mass inflow rate and supernova feedback affect the ring star formation rate. The supernova feedback is responsible for small-amplitude SFR fluctuations with a timescale of less than 40 million years, while the SFR variations over longer timescales are due to changes in the mass inflow rates. Magnetic fields seeded by the inflows are amplified in the ring due to rotational shear and supernova feedback, greatly reducing the SFR at late times. Strong magnetic tension in the ring drives radially inward accretion flows from the ring to form a circumnuclear disk in the central region, which is absent in the unmagnetized model.